Measuring dimensionality and purity of high-dimensional entangled states - Isaac Nape (Nature Portfolio, 2021)
Quantifying dimensionality of high-dimensional entangled states is challenging, especially in the presence of mixedness and noise. Here, the authors propose and demonstrate a method to quantify the dimensionality and purity of a bi-photon HD entangled state, scaling linearly with entanglement dimension.